PENGEMBANGAN MODUL INKUIRI TERBIMBING BERBASIS POTENSI LOKAL PADA MATERI TUMBUHAN LUMUT (BRYOPHYTA ) DAN TUMBUHAN PAKU (PTERIDOPHYTA) - Novana, Tri -; -, Sajidan -; -, Maridi - (Jurnal Inkuiri, 2014)
The objectives of this research were to develop an Guided Inquiry Module Based on Local Potentials to  Bryophyte and Pteridophyte Materials, to know feasibility an Guided Inquiry Module Based on Local Potentials to  Bryophyte and Pteridophyte Materials, and to distinguish an Guided Inquiry Module Based on Local Potentials to  Bryophyte and Pteridophyte Materials on the  learning achievement of X class students and baseline class. Research  method used were Research and Development. Steps of this work were as follows: analyzing  the problems and potentials of the development of  Guided Inquiry Module Based on Local Potentials to  Bryophyte and Pteridophyte Materials,  collecting data, designing a particular product, validating the products  by experts,  and empirically  testing products for  mass production. The population were all student in grade Xth State Senior High School 3 Surakarta academic year 2012/2013. Learning Implementation using 3 classes that were  grade X1, X3, and X5. The 1th class, grade X1 learnt using local potentials inquiry based module and 2th class, grade X3 using conventional learning, and grade X5 learnt using local potentials inquiry based module, collaborative inquiry model.  The data analized by descriptive statictic. Guided Inquiry Module Based on Local Potentials to  Bryophyte and Pteridophyte Materials developed by analyzing  the problems and potentials of the development of Guided Inquiry Module Based on Local Potentials to  Bryophyte and Pteridophyte Materials,  collecting data, designing a particular product, validating the products  by experts,  and empirically  testing products for  mass production. A Guided Inquiry Module Based on Local Potentials to  Bryophyte and Pteridophyte Materials  was finally developed under  the proper criteria, meaning that a Guided Inquiry Module Based on Local Potentials to  Bryophyte and Pteridophyte Materials was feasible as learning source. The use of a Guided  Inquiry Module Based on Local Potentials to  Bryophyte and Pteridophyte Materials brought  good  effect on student learning achievement.